A European Public Investment Outlook - CERNIGLIA, FLORIANA MARGHERITA; Saraceno, Francesco (Open Reports Series, 2020)
"This outlook provides a focused assessment of the state of public capital in the major European countries and identifies areas where public investment could contribute more to stable and sustainable growth. A European Public Investment Outlook brings together contributions from a range of international authors from diverse intellectual and professional backgrounds, providing a valuable resource for the policy-making community in Europe to feed their discussion on public investment. The volume both offers sector-specific advice and highlights larger areas which should be prioritized in the policy debate (from transport to social capital, R&D and the environment). The outlook is structured into two parts: the chapters of Part I respectively explore public investment trends in France, Germany, Italy, Spain and Europe as a whole, and illuminate how the legacy of the 2008 Global Financial Crisis is one of insufficient public investment. Part II investigates some areas into which resources could be channelled to reverse the recent trend and provide European economies with an adequate public capital stock. The essays in this outlook collectively foster a broad approach to and definition of public investment, that is today more relevant than ever. Offering up a timely and clear case for the elimination of bias against investment in European fiscal rules, this outlook is a welcome contribution to the European debate, aimed both at policy makers and general readers"